Lipoprotein combine index is associated with non-alcoholic fatty liver disease: a 5-year longitudinal cohort study in non-obese Chinese populations with normal lipids - Wu, Weitao; Wu, Donghai; Cao, Changchun; Zhou, Ronghua; Ding, Shihua; Ying, Ying; Sun, Dayong; Hu, Haofei (Frontiers in Medicine, 2025)
ObjectiveCurrent evidence concerning the association between lipoprotein combine index (LCI) and Non-alcoholic fatty liver disease (NAFLD) in non-obese people remains limited. This 5-year longitudinal cohort study aimed to explore the connection between LCI and risk of NAFLD in non-obese Chinese individuals with normal lipids.MethodsThis retrospective cohort study from January 2010 to December 2014 consecutively and non-selectively collected 9,838 non-obese participants with normal lipid profiles in a Chinese hospital. Using the Cox proportional-hazards regression model, we explored the relationship between baseline LCI and NAFLD risk. We applied cubic spline functions and curve fitting to characterize the non-linear association between LCI and NAFLD. Simultaneously, we conducted sensitivity and subgroup analyses, and employed receiver operating characteristic (ROC) curve analysis to evaluate the predictive potential of LCI for NAFLD incidence.ResultsThe mean age of participants was 42.46 ± 14.70 years, with males comprising 51.40% of the cohort. During a median follow-up period of 33.10 months, 855 participants (8.89%) progressed NAFLD, with an incidence of 31.51 cases per 1,000 person-years. A significant non-linear relationship was identified between LCI and NAFLD risk with an inflection point at 5.514 mmol2/L2, where the HR was significantly stronger below this threshold (HR = 1.282, 95%CI: 1.162–1.415) compared to above it (HR = 1.063, 95%CI: 1.042–1.084). Subgroup analysis revealed the strongest associations in participants with body mass index (BMI) between 18.5 and 24 kg/m2. LCI demonstrated superior predictive value for NAFLD compared to individual lipid parameters, with an area under the ROC curve of 0.717.ConclusionThis study offers novel insights into the relationship between LCI and NAFLD risk in non-obese Chinese individuals with normal lipid levels. The non-linear association and the moderate discriminatory ability of LCI suggest its potential utility as a practical screening marker for population-level risk stratification and early preventive strategies in seemingly low-risk, normal-weight populations.